Correction: Effect of heterocycle content on metal binding isostere coordination. Issue 12 (8th March 2022) - Dick, Benjamin L.; Patel, Ashay; Cohen, Seth M.
Abstract : Correction for 'Effect of heterocycle content on metal binding isostere coordination' by Benjamin L. Dick et al., Chem. Sci., 2020, 11, 6907–6914, DOI: ; 10.1039/D0SC02717K .